Load Balancing in Cloud Systems Using Dynamic Chained Failover Algorithm - Sangeetha, M.; K.Senthil Kumar, K.; Parimala, G. (International Journal of Engineering and Technology, 2018)
Large-scaled cloud systems have been there in various domains by extendinglarge number of resources. Efficient allocation of shared assets in cloud is a vital but provocative issue. It is known that existing load balancing policies like Random,size-based polices, Join Shortest Queue are implemented in cloud as they are simple and efficient. The performance of the above mentioned policies decrease when workloads are temporally correlated. We propose the new load balancing method, Dynamic Chained Failover Algorithm in this paper where particular time period at which the server is getting overloaded is taken and particular task which causes overloading in particular interval is placed in all servers as a replica instead of data reallocation. Overall system performance is increased. Exploiting capable server to improve the system performance is thus demanded.Â Â